Design of Coherent Envelope Measurement Circuit Based on Direct Digital Frequency Synthesizer - Jbari ATMAN; Larbi BELLARBI; Abdelhamid ERRACHID (International Journal of Applied Methods in Electronics and Computers, 2016)
Envelope detection and measurement has important applications in many   domains such as instrumentation, sensors characterization, analog and digital communications. Instead of other envelope detection methods that use analog circuits or digital filters, we propose an electronic circuit that operates measurement in coherent mode. After reproduction of the input wave frequency using direct digital synthesizers, we place the envelope on a new low reference frequency signal followed by an analog measurement block based on analog multipliers and low-pass filters. Design circuit, simulation and experimental results are presented to validate the measurement for different values of input and reference frequencies.